Mexican and Hispanic Net Nutrition in the 19th Century American West - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2015)
When traditional methods for measuring economic welfare are scarce or unreliable, heights and BMIs are now well accepted measurements that represent biological conditions during economic development. Weight, after controlling for height, is an alternative measure to BMI for current net nutrition. Little is known about how weights varied among Mexicans living in the 19th century American West. Between 1870 and 1920, average Mexican weight decreased slightly. Mexican farmers had the heaviest weights, and unskilled worker weights were low. For combined characteristics, weight varied the most with height and age, two uncontrollable characteristics, indicating that 19th century Mexican current net nutrition varied the most with factors over which individuals of Mexican descent had no control.
Keywords: I10; J11; J15; N00; N31; 330; anthropometrics; nineteenth century US weights; net nutrition; health